2021
DOI: 10.1111/pde.14792
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric hematidrosis – A case report and review of the literature and pathogenesis

Abstract: Hematidrosis is a disorder in which blood-tinged fluid exudes from uninjured skin or mucosa. It is often classified as an eccrine sweat disorder, though the precise mechanism-including involvement of sweat glands-has yet to be proven. In contemporary case reports, hematidrosis appears most frequently in the pediatric population, with 83% of cases in the literature since 2008 occurring in individuals 18 years old or younger. We present here a case of a 10-year-old girl with hematidrosis followed by a review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…The second is that most patients improve or go into remission after taking beta-blockers and/or antidepressants, antianxiolytics, or psychotherapy [ 2 ]. According to a literature review done in 2021, treatment with beta-blockers had an effectiveness of up to 94%, while psychotherapy (including cognitive-behavioral therapy, relaxation techniques, and family education) had an effectiveness of 66% [ 5 ]. Idiosyncratically, our patient was a 20-year-old female, unlike the usual age presentation of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second is that most patients improve or go into remission after taking beta-blockers and/or antidepressants, antianxiolytics, or psychotherapy [ 2 ]. According to a literature review done in 2021, treatment with beta-blockers had an effectiveness of up to 94%, while psychotherapy (including cognitive-behavioral therapy, relaxation techniques, and family education) had an effectiveness of 66% [ 5 ]. Idiosyncratically, our patient was a 20-year-old female, unlike the usual age presentation of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Idiosyncratically, our patient was a 20-year-old female, unlike the usual age presentation of the disease. It has been reported that 83% of hematohidrosis patients present at age 18 and younger [ 5 ]. Although our case involved a Saudi female, hematohidrosis has been rarely reported in the region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematidrosis is an exceedingly rare and peculiar clinical disorder characterized by spontaneous exudation of blood-mixed fluid from the intact skin or mucosa. [ 1 2 ] Though fewer than hundred cases have been reported so far,[ 1 2 3 4 5 ] its mention dates back to the era of Leonardo da Vinci and notably in Bible too. [ 3 ] It has been mainly cited in dermatological texts,[ 1 2 3 ] whereas management involves mostly psychotropics, beta blockers, and psychotherapy.…”
Section: Introductionmentioning
confidence: 99%